Can percutaneous cholecystostomy be a definitive treatment in the elderly?. Issue 4 (November 2016) - Solaini, Leonardo; Paro, Barbara; Marcianò, Paolo; Pennacchio, Giacomo V.; Farfaglia, Roberto
Abstract : Aim: The aim of the present study was to discuss our experience with percutaneous cholecystostomy (PC), analysing the outcomes and investigating the clinical factors, which might predict the future need for surgery. Patients and Methods: Forty‐two patients with acute calculous cholecystitis underwent PC over a 122‐month period at a single institution. Patients' demographics, clinical features and management were retrospectively analysed. Results: There were 20 females (47.6 per cent) and 22 males (52.4 per cent), with a median age of 83 years (interquartile range: 75–87 years). The American Society of Anesthesiologists (ASA) score was III for 7 patients and IV for 35 patients. Thirty‐one patients (71.4 per cent) had moderate cholecystitis, and 11 (26.2 per cent) had severe cholecystitis. During the index admission, six patients (14.2 per cent) required endoscopic retrograde cholangiopancreatography (ERCP), cholecystectomy was performed in three (7.2 per cent) and four patients (9.5 per cent) died due to septic shock. Nine patients were readmitted for recurrent biliary symptoms, and six of them underwent cholecystectomy. All patients who underwent cholecystostomy and ERCP did not have any recurrence and/or cholecystectomy. The Charlson Comorbidity Index score was significantly higher in patients who did not have subsequent surgery (9 vs 7, P = 0.02). Conclusions: PC can be a valuable treatment option for high‐risk patients, and a definitive treatment for the elderly with high CCI. Patients who have undergone PC and ERCP might have a lower probability to develop recurrent biliary symptoms than those who have undergone PC alone.